The Residuum of Childhood Physical and Sexual Abuse: Coming to Terms in Couple Relationships. Issue 9 (May 2022) - Banford Witting, Alyssa; Busby, Dean M.
Childhood exposure to physical violence and sexual abuse is a public health concern and is empirically connected to poor outcomes in adulthood. The present study was designed to assess dyadic associations between exposure to childhood physical violence and sexual abuse, and resolution, or a sense that one has "come to terms" with events in one's family of origin. The study was also aimed at assessing whether attachment behaviors mediated associations between abuse, violence, and resolution. The study was carried out using data from a community sample of 3, 836 heterosexual couples who completed the Relationship Evaluation Questionnaire inventory. Actor–Partner Interdependence Modeling was employed within a structural equation model to examine associations. Results suggested inverse, direct actor associations for both men and women between physical violence and sexual abuse, and coming to terms. The results also showed inverse, direct partner associations for both men and women between sexual abuse and coming to terms. Furthermore, findings indicated the presence of inverse, indirect actor and partner effects for men and women between physical violence and coming to terms. Examination of these specific indirect partner and actor effects from physical violence to coming to terms implies partial mediation carried through one's own rating of attachment behaviors. Finally, actor (but not partner) associations were noted between attachment behaviors and coming to terms. In aggregate, the findings support the potential benefit of enhancing investment in attachment behaviors as a resource to aid in the resolution process of exposure to physical violence and sexual abuse in childhood.